The Miedzianka Mountain Ore Deposit (Świętokrzyskie Mountains, Poland) as a Site of Historical Mining and Geological Heritage: A Case Study of the Teresa Adit - Agnieszka Ciurej (MDPI AG, 2021)
There are numerous traces of mining activity in the Miedzianka Mountain (Świętokrzyskie Mountains, Poland), because copper and silver ores have been mined in this region since at least the 13th century. The history of scientific research on the Miedzianka Mountain ore deposit spans almost 200 years. Almost 40 minerals have been found: ore minerals of Cu and Fe, and also secondary minerals, including carbonates, sulphates and even very rare arsenates, phosphates and vanadates. Three new minerals have been found, staszicite, lubeckite and miedziankite, but their chemical composition has not been precisely determined and therefore their names have not been approved by the International Mineralogical Association (IMA). The Miedzianka Mountain deposit is an important area on the map of educational activities. It is included in the “Świętokrzyskie Archaeological and Geological Trail” as a site of historical (mining and metallurgy) and natural (geological sciences) heritage. Despite the large potential, none of the underground workings (adits and shafts) are currently available to the public. Our research and exploration of the Teresa adit, which is one of the historical underground complexes of the Miedzianka Mountain, show that this adit displays a wide spectrum of topics in the field of mineralogy, geology and mining history. The Teresa adit, which is a 523 m system of underground corridors, contains 270 m of natural karst caves altered by mining works and is constituted of Upper Devonian limestones, locally cut by cherry shales. In several sites of the adit unique features can be observed, such as: (1) old mining works—galleries carved in the rock back in the 19th century; (2) interesting vein mineralization with secondary-colored copper carbonates and multi-colored calcite veins; (3) mineralization with azurite domination; and (4) karst phenomena (coatings, flowstone, dripstones and stalactites) in a cave part of the adit. The sites with unique features suggest that the Teresa adit is highly suitable to be presented to tourists. That is why we propose seven sites on the underground route that could be the basis for further projects to create a “geotouristic trail” in the Teresa adit. The proposal to make the Teresa adit available to tourists is in line with the tendency to protect the post-industrial landscape associated with former mining activities.